RESULTS OF THE FIRST YEAR OF THE PROJECT ``IVOS'' - Milan, KLEMENT; LAVRINCIK, Jan (Trends in education, 2010)
The article presents the results and outputs of activities undertaken within the first year of the project Ivos - improving the quality of education by introducing interactive teaching in schools, which is funded by the European Social Fund and the Czech state budget.
Keywords: interactive whiteboards; project activities; systematic training; training modules; interactive lessons.